CP violation arising from particle-antiparticle mixing - Ping, Chia Swee (Malaysian Journal of Science, 1995)
Indirect CP violation arising from particle-antiparticle mixing is calculated from the box diagrams in the Standard Model for KO—KO, BO—BO and Bs0—B? systems. The CP violation parameter for each of the systems is shown to be closely related to the relative phases of the Kobayashi-Maskawa matrix elements.